2015
DOI: 10.1111/jdi.12397
|View full text |Cite
|
Sign up to set email alerts
|

Association of chemokine ligand 5/chemokine receptor 5 gene promoter polymorphisms with diabetic microvascular complications: A meta‐analysis

Abstract: Aims/IntroductionChemokine ligand 5 (CCL5) is a member of the CC‐chemokine family expressed in various organs. It contributes to the migration of monocytes/macrophages into injured vascular walls by binding with its receptor chemokine receptor 5 (CCR5). Many studies have accessed the association between CCL5/CCR5 gene promoter polymorphisms and diabetic microvascular complications (DMI). However, the results are conflicting and inconclusive. The aim of the present study was to evaluate the association more pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Its gene is located on the short arm of chromosome 3 (3p21.31) [11] at the promoter region. Though there are conflicting and inconclusive reports on the association of CCR5 gene promoter polymorphism with the risk of DN, the polymorphism in CCR5 might affect individual susceptibility to DN [12]. The gene, however, has been reported to have an association to nephropathy in T2DM among the Japanese and Asian Indian population [1316].…”
Section: Introductionmentioning
confidence: 99%
“…Its gene is located on the short arm of chromosome 3 (3p21.31) [11] at the promoter region. Though there are conflicting and inconclusive reports on the association of CCR5 gene promoter polymorphism with the risk of DN, the polymorphism in CCR5 might affect individual susceptibility to DN [12]. The gene, however, has been reported to have an association to nephropathy in T2DM among the Japanese and Asian Indian population [1316].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that CCR5-59029 G/A was an independent risk factor for DKD (Yahya et al, 2019). The CCR5 59029A-positive genotype was correlated with an increased risk for albuminuria (Zhang et al, 2016). Mlynarski et al (2005) showed that the CCR5-D32 mutation increased the risk of kidney disease in men with type 1 diabetes; however, this outcome is contrary to that of Prasad et al (2007) who found that CCR5-D32 was not related to nephropathic type 2 diabetes patients.…”
Section: Hyperglycemiamentioning
confidence: 79%
“…All of the genetic markers were selected based on previous reports. The inclusion criteria of candidate SNPs were set as a combined P < 10 −4 for GWAS 18 , 19 , 23 , 29 and a P < 0.05 for meta-analysis 20 , 21 , 30 50 . A total of 58 SNPs in 44 susceptibility loci were evaluated in our study (details are summarized in Table S1 ).…”
Section: Methodsmentioning
confidence: 99%